Navigating Turbulence: India’s Economic Corridor Amid Middle Eastern Conflicts - Chowdhury, Sudeshna (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This article discusses the India-Middle East-Europe Economic Corridor (IMEC) as a game changer in world trade and geo-strategic realignment. It examines the potential of the corridor to facilitate further connectivity, lower trade costs, and promote economic integration between Asia, the Middle East, and Europe. Rooted in liberal and realist international theories, the paper sketches advantages of interdependence and disadvantages created by regional conflicts, great-power rivalry, and the exclusion of pivotal states, including Iran and Turkey. The study raises major challenges, including the Israel–Hamas conflict and persistent Middle Eastern instability, but offers ideas to improve efforts of policy coordination, inclusive governance, and adaptive diplomacy. In the end, the article contends, IMEC’s prospects primarily hinge on the durability of collective action, organizational ingenuity, and continuous stakeholder activism in order to surmount the all too familiar geo-political headwinds and materialize its promise as a new trade lifeline connecting continents.